The Role of Accommodation and Food Service Industry to The Development of Tourism In Jawa-Bali - Wahyu Hidayati; Ihda Arifin Faiz (EKO-REGIONAL, 2020)
The Role of Accommodation and Food Service Industry which is measured by its contribution, employment and its affecting factors, employment elasticity, as well as labor productivity towards economy, particulary tourism, has not been optimised. This research aims to analyse: (1) the impact of Provincial Minimum Wage (PMW), Gross Regional Domestic Product (GRDP), the Number of Businesses, and Inflation on employment in Accommodation and Food Service Industry; (2) its contribution toward economy, employment, employment elasticity, and labor productivity in the given industry. The analytical tools used in this research are Descriptive Statistics and Pooled Data Regression Model (FEM and REM Approaches). The data being analysed is secondary data series 2014-2018 and cross sectional which is taken (provinces in Jawa-Bali) and respective to this research problem and goal. The result shows that the factors influencing employment rate positively and significantly are GRDP and inflation, whilst those affecting insignificantly are PMW and the number of businesses. The average contribution during 2015-2018 was 7.43% annually, whereas in Bali and DIY, the contribution was 23.17% and 10.21%, respectively. The employment rate per business averaged to 497 people with the average growth of employment in the given industri of about 14.22% annually. The employment elasticity  was 0.63 and labor productivity per person averaged to IDR 84.99 million higher than national average of IDR 53.84 million/person in 2018. Consequently, in order to increase output, high multiplier effect in economy, stable inflation (3%-4% annually), and prudential PMW policy are required